Zonotopic set-membership estimation for Switched Systems based on Wi-Radius Minimization: Vehicle application. Issue 2 (2020) - Ifqir, Sara; Puig, Vicenç; Ichalal, Dalil; Ait-Oufroukh, Naima; Mammar, Saïd
Abstract: This work is devoted to the problem of guaranteed set-membership state estimation based on zonotopes for discrete-time switched systems with bounded uncertainties and unknown inputs. The additive uncertainties in this contribution are treated using the so called Wi -Radius. The size of the zonotope which contains the real system state is decreased at each sample time. The complete solution procedure is formulated as a LMI-constrained optimization problem. The proposed design is applied to the robust state estimation of vehicle lateral dynamics state. Simulation results based on real data demonstrate the performance of the proposed method.